Using a Digital Language Processor to Quantify the Auditory Environment and the Effect of Hearing Aids for Adults with Hearing Loss - Klein, Kelsey E.; Wu, Yu-Hsiang; Stangl, Elizabeth; Bentler, Ruth A. (Journal of the American Academy of Audiology, 2018)
Auditory environments can influence the communication function of individuals with hearing loss and the effects of hearing aids. Therefore, a tool that can objectively characterize a patient’s real-world auditory environments is needed.To use the Language Environment Analysis (LENA) system to quantify the auditory environments of adults with hearing loss, to examine if the use of hearing aids changes a user’s auditory environment, and to determine the association between LENA variables and self-report hearing aid outcome measures.This study used a crossover design.Participants included 22 adults with mild-to-moderate hearing loss, age 64–82 yr.Participants were fitted with bilateral behind-the-ear hearing aids from a major manufacturer.The LENA system consists of a digital language processor (DLP) that is worn by an individual and records up to 16 hr of the individual’s auditory environment. The recording is then automatically categorized according to time spent in different types of auditory environments (e.g., meaningful speech and TV/electronic sound) by the LENA algorithms. The LENA system also characterizes the user’s auditory environment by providing the sound levels of different auditory categories. Participants in the present study wore a LENA DLP in an unaided condition and aided condition, which each lasted six to eight days. Participants wore bilateral hearing aids in the aided condition. Percentage of time spent in each auditory environment, as well as median levels of TV/electronic sounds and speech, were compared between subjects’ unaided and aided conditions using paired sample t tests. LENA data were also compared to self-report measures of hearing disability and hearing aid benefit using Pearson correlations.Overall, participants spent the greatest percentage of time in silence (∼40%), relative to other auditory environments. Participants spent ∼12% and 26% of their time in meaningful speech and TV/electronic sound environments, respectively. No significant differences were found between mean percentage of time spent in each auditory environment in the unaided and aided conditions. Median TV/electronic sound levels were on average 2.4 dB lower in the aided condition than in the unaided condition; speech levels were not significantly different between the two conditions. TV/electronic sound and speech levels did not significantly correlate with self-report data.The LENA system can provide rich data to characterize the everyday auditory environments of older adults with hearing loss. Although TV/electronic sound level was significantly lower in the aided than unaided condition, the use of hearing aids seemed not to substantially change users’ auditory environments. Because there is no significant association between objective LENA variables and self-report questionnaire outcomes, these two types of measures may assess different aspects of communication function. The feasibility of using LENA in clinical settings is discussed.
Keywords: auditory environment; hearing aids; hearing loss; patient outcome assessment